CBD vs. Casino : how Brazil's biggest retailer fought a French governance takeover - and lost - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
Brazilian retail markets had been a tempting arena for growth-minded companies since the country instituted democratic reforms in the 1980s. To raise capital for continued expansion, Abilio Diniz, the billionaire chairman of Brazil's number-one retailer Companhia Brasileira de Distribuic'ao (CBD), entered a long-term agreement in 2005 to transfer control of the retail empire to the CEO of the French retailer Casino Guichard-Perrachon SA in 2012. This case examines why the deal failed.